Pengaruh Penerapan Metode Pembiasaan terhadap Perkembangan Nilai Agama dan Moral Anak Usia 4-5 Tahun di SPS Kartika - Nurhaedah, Nurhaedah; Mulyani, Endang; Hidayat, Yusuf; Rosidah, Lela (JOECE: Journal of Early Childhood Education, 2025)
Instilling religious and moral values is very important applied as the basis life for growing early childhood's noble character. This study aims to determine the development of religious and moral values ​​of early childhood aged 4-5 years before and after using the habituation method, as well as to determine the effect of applying habituation method on the development of religious and moral values ​​of early childhood aged 4-5 years at SPS Kartika. This study used a quantitative method under a pre-experimental design. The results of the study showed that before being given treatment in the form of applying habituation method, the development of religious and moral values ​​of early childhood aged 4-5 years at SPS Kartika showed “Starting to Develop” (MB). Furthermore, after being given treatment in the form of applying habituation method, the development of religious and moral values ​​of early childhood aged 4-5 years at SPS Kartika showed “Developing Very Well” (BSB). Then, based on the results of the t-test, it was stated that t-observed > t-table, at which the scores were 12.5 > 2.093 under a significance level of 0.05. The comparative scores indicated that H0 was rejected and H1 was accepted. It confirms that the use of habituation method has a significant influence on the development of the early childhood’s aged 4-5 years religious and moral values at SPS Kartika.